2002
DOI: 10.1021/jp021008t
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Angle X-ray Scattering Study of Complexes Formed in Mixtures of a Cationic Polyelectrolyte and an Anionic Surfactant

Abstract: The internal structure of the solid phase formed in mixtures of the anionic surfactant sodium dodecyl sulfate (SDS) and a range of oppositely charged polyelectrolytes with different side chains and charge density has been investigated using small-angle X-ray scattering. Polyelectrolytes with short side chains ([3-(2-methylpropionamido)propyl]trimethylammonium chloride, MAPTAC, and poly{[(2-propionyloxy)ethyl]trimethylammonium chloride}, PCMA) form a 2-dimensional hexagonal structure with SDS, whereas a polyele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
43
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 26 publications
9
43
0
Order By: Relevance
“…We suggest that the much smaller size of the PCMA-SDS complex at low surfactant concentrations is due to the extra induction of hydrophobicity by SDS to the complex, which together with a reduction in the charge density, enable denser packing in the interior of the polyelectrolyte-surfactant complex. In fact, SANS and SAXS studies [29,31] have shown that the interior of the aggregates formed close to the charge neutralization point consists of cylindrical SDS micelles wrapped by polyelectrolyte arranged in a hexagonal organization. The water layer thickness, including the surfactant head group and the polyelectrolyte, between these structural units has been estimated to be 1.6 nm [31].…”
Section: Dynamic Light Scattering Measurements Shortly After Mixingmentioning
confidence: 99%
See 3 more Smart Citations
“…We suggest that the much smaller size of the PCMA-SDS complex at low surfactant concentrations is due to the extra induction of hydrophobicity by SDS to the complex, which together with a reduction in the charge density, enable denser packing in the interior of the polyelectrolyte-surfactant complex. In fact, SANS and SAXS studies [29,31] have shown that the interior of the aggregates formed close to the charge neutralization point consists of cylindrical SDS micelles wrapped by polyelectrolyte arranged in a hexagonal organization. The water layer thickness, including the surfactant head group and the polyelectrolyte, between these structural units has been estimated to be 1.6 nm [31].…”
Section: Dynamic Light Scattering Measurements Shortly After Mixingmentioning
confidence: 99%
“…In fact, SANS and SAXS studies [29,31] have shown that the interior of the aggregates formed close to the charge neutralization point consists of cylindrical SDS micelles wrapped by polyelectrolyte arranged in a hexagonal organization. The water layer thickness, including the surfactant head group and the polyelectrolyte, between these structural units has been estimated to be 1.6 nm [31].…”
Section: Dynamic Light Scattering Measurements Shortly After Mixingmentioning
confidence: 99%
See 2 more Smart Citations
“…[9,10] Ionic polymers having similar charge with the surfactant molecules show moderate effect however, polymers having an opposite charge may cause more important effects in surfactant solutions. [1,11] Among the branched polymers, polyethyleneimine (PEI) is of special interest because it is widely used as dispersion stabilizer, flocculation agent, adhesive, and in gene delivery therapy. [12,13] Similarly, SDS is an anionic surfactant that is commonly used in mineral processing, flotation, and manufacturing many chemical products.…”
Section: Introductionmentioning
confidence: 99%